Dynamic jump intensities and risk premiums: Evidence from S&P500 returns and options - Christoffersen, Peter; Jacobs, Kris; Ornthanalai, Chayawat (Journal of Financial Economics, 2012)
We build a new class of discrete-time models that are relatively easy to estimate using returns and/or options. The distribution of returns is driven by two factors: dynamic volatility and dynamic jump intensity. Each factor has its own risk premium. The models significantly outperform standard models without jumps when estimated on S&P500 returns. We find very strong support for time-varying jump intensities. Compared to the risk premium on dynamic volatility, the risk premium on the dynamic jump intensity has a much larger impact on option prices. We confirm these findings using joint estimation on returns and large option samples.